Project management during covid-19: the relevance of human skills and the infrastructure project performance in Klang Valley Malaysia - Priyadarsini, Palaniapan (2023)
Historically, one of the keys streamlining projects in Malaysia's construction industry has been infrastructure, and the government serves as the primary employer for a variety of projects that are frequently undertaken. The government supports a number of national development plans with significant funding. Despite the huge allocation of the funding ,many of them have underperformed, mostly as a result of a shortage of human skills. The covid-19 pandemic, which has impacted the entire world and caused an economic collapse, has made matters far worse. The aim of this study is to analyse the relevance of human skills and their efficacy on the infrastructure project perforance in Klang Valley, Malaysia during covid-19 pandemic and simultaneously to analyse the training and development in the infrastructure project performance during the pandemcic. The quantitative genre investigation used a survey questionanaire with closed-ended questions, administered to construction professionals involved in infrastucture projects during the covid-19 pandemic, aiming to collect valuable data for subsequent analysis. The results indicate that the efficacy of human skillsin the realm of project management activities within infrastructure projects during the covid-19 pandemic is shaped by key human skills and strategic training and development. The significance of human skills and their relevance on infrastructure project performance is noteworthy, with training playing a pivotal role in developing these skills. The implication of this study centres on the accomplishments of all the research objectives, while bridging the knowledge gap on the subject, as this research provides a comprehensive perspective on the relevance of human skills in infrastructure projects. It also sheds light on the unique role of human skills in the performance of infrastructure projects and the importance of training, beyond technological advancements and project management methodologies.